Current practices and future outlook on the integration of biomarkers in the drug development process. (December 2017) - Fraser, Stephanie; Osgood, Sarah
Over the last decade, there has been broad incorporation of translational biomarkers into the early drug development process to predict safety concerns, measure target engagement and monitor disease progression. One goal of translational biomarkers is to create a cycle whereby preclinical readouts influence candidate selection and subsequent clinical data are fed back into research to facilitate better decision making. Successes have been limited and not as broad in scope as desired. Collaborations between industry and regulators have increased the number of qualified biomarkers; but the process is lengthy and expensive. A high level overview of translational biomarkers as well as a discussion of some of the successes and failures encountered in development is discussed here.